Large-eddy simulation of cultivated fields with Cyperus malaccensis Lam - Moe Shiraishi; Hiroaki Hayashi; Hiroaki Shimada; Shin-Ichi Satake (Plant Production Science, 2023)
ABSTRACTIn this study, the honami phenomenon in Cyperus malaccensis Lam. was reproduced to establish a simulation technique that can accurately reproduce the waves of it and predict the wind flow over it and through it, which is related to its growth. The analysis code was constructed on the basis of a large-eddy simulation (LES). The LES model is based on the nonrotating coherent-structure Smagorinsky model (NRCSM), which is an expansion of the Smagorinsky model. In addition, this code is solved for a bundle of reaped rice plants, which are based on the vegetation movement, using the Newmark-beta method with an LES to analyze the movement of vegetation and air in the field. As a result, vortex structures and vegetation oscillations were visualized. We observed not only the streamwise vortex structures near the tips of C. malaccensis Lam. but also characteristic structures that sink into the vegetation simultaneously with vegetation shaking. Consequently, we found that the vibration of C. malaccensis Lam. is influenced by air inflow within the planting.